APPLICATION MODELING STUDY ON THE IMPROVEMENT OF LEARNING DRIBLING FOOTBALL (STUDIES IN CLASS V PUBLIC PRIMARY SCHOOLS KEDAMEAN 2 GRESIK) - SUGATOT, DIDIK (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In the implementation of physical education in school learning in general is still very dominant role of the teacher so that students receive a lesson and they just can not learn according to its development stage. Therefore it should be given a more varied learning models such as, the application of the use of learning medel modeling so that students are expected to play an active role in any learning process. So also happens to fifth grade students of Public Primary Schools Kedamean 2 Gresik, initial observations indicate as many as 82,9% of students have a low ability to dribling at football game. This happens due to lack of material delivered maximum message that teachers can be understood by students, and therefore required a more effective and efficient to solve the problem. The purpose of this study was to determine: 1) improved learning outcomes dribling football with modeling learning model in class V Public Primary Schools Kedamean 2 Gresik, 2) large increase in learning outcomes dribling football with modeling learning model. Objectives of this study were fifth grade students of Public Primary Schools 2 Gresik Kedamean by the number of students by 41 students. This type of research is a classroom action research (CAR), which are continuous and continuously from cycle to cycle. Data was collected through observation and measurement of student learning outcomes in each cycle. Assessment of learning outcomes measured include: aspects of psychomotor, cognitive, and affective. Conclusion: 1) The use of modeling in teaching learning medel football may actually enhance learning outcomes dribling football Kedamean fifth grade students of Public Primary Schools 2 Gresik. This can be seen in the graphs or tables 4.1 and 4.2 where the average class at 4.18 each learning cycle has increased. 2) At the beginning of the study before treatment is given the mean value of classroom learning outcomes are achieved 56,9 increased by 15,9% to 65,95 in Cycle 1. Then in the second cycle looks no increase 16,2% from cycle 1. So that the average value of grade 2 cycle achieved by 76,7. Developmental outcomes classical completeness students from the initial study (17,1%) to the first cycle (36,6%) seen an increase of 19,5% and from cycle 1 (36,6%) to cycle 2 (73,2%) increased by 36,6%. Keywords: Learning, Modeling, Dribling Football.